Kualitas Layanan pada Pelayanan Kesehatan Kabupaten Sampang - Jannah, Salamatun; Andriani, Nurita (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This study aims to find out whether there is an influence of physical evidence, responsivenes, reliability, assurance, and emphaty on patient satisfaction at the Torjun Public Health Center, Sampang Regency. This type of research is quantitative research.  In this study, the samples taken were patients at the Torjun Public Health Center, Sampang Regency was 100 patients.  The sampling method is purposive sampling.  The data collection technique used is a questionnaire technique.  The results of the research prove that physical evidence, responsiveness, assurance and empathy have a significant effect on patient satisfaction at the Torjun Public Health Center, Sampang Regency.  Meanwhile, the research results for the reliability did not have a significant effect on patient satisfaction at the Torjun Public Health Center, Sampang Regency.  And the most influence on patient satisfaction at the Torjun Sampang Public Health Center is the assurance.